Engineering Production of a Novel Diterpene Synthase Precursor in Nicotiana benthamiana - Forestier, Edith C. F.; Brown, Geoffrey D.; Harvey, David; Larson, Tony R.; Graham, Ian A. (Frontiers in Plant Science, 2021)
Diterpene biosynthesis commonly originates with the methylerythritol phosphate (MEP) pathway in chloroplasts, leading to the C20 substrate, geranylgeranyl pyrophosphate (GGPP). Previous work demonstrated that over-expression of genes responsible for the first and last steps in the MEP pathway in combination with GERANYLGERANYL PYROPHOSPHATE SYNTHASE (GGPPS) and CASBENE SYNTHASE (CAS) are optimal for increasing flux through to casbene in Nicotiana benthamiana. When the gene responsible for the last step in the MEP pathway, 4-HYDROXY-3-METHYLBUT-2-ENYL DIPHOSPHATE REDUCTASE (HDR), is removed from this combination, casbene is still produced but at lower amounts. Here we report the unexpected finding that this reduced gene combination also results in the production of 16-hydroxy-casbene (16-OH-casbene), consistent with the presence of 16-hydroxy-geranylgeraniol phosphate (16-OH-GGPP) in the same material. Indirect evidence suggests the latter is formed as a result of elevated levels of HMBPP caused by a bottleneck at the HDR step responsible for conversion of HMBPP to DMAPP. Overexpression of geranyllinalool synthase from Nicotiana attenuata produces 16-hydroxy-geranyllinalool (16-OH-geranyllinalool) when transiently expressed with the same reduced combination of MEP pathway genes in N. benthamiana. This work highlights the importance of pathway flux control in metabolic pathway engineering and the possibility of increasing terpene diversity through synthetic biology.